Socialization of the Implementation of ISAK 335 in Orphanages in Medan City - Sahala Purba; Septony B Siahaan; Kuras Purba; Wie Shi Wudjud; Santy Aji Sitohang (LPPI Yayasan Almahmudi bin Dahlan, 2025)
The purpose of this service is so that every orphanage in Indonesia, especially in Medan City, can implement ISAK 335 in preparing its financial reports, so that large donors can trust the money they donate to the orphanage. The method used in this socialization is by interviewing first, then conducting socialization of accounting records to financial reporting in accordance with the provisions in force in Indonesia. The place of this socialization was carried out at the Full Hope Orphanage located on Jl. Pembangunan, Beringin, Medan Selayang District, Medan City. And the Pelita Harapan Orphanage located on Jalan Piala, No. 21A Sei Putih Tengah, Medan Petisah. The implementation time was December 8-9, 2024. The result of this socialization was that the orphanage owners felt awkward because so far they did not know that there were special financial reporting standards for orphanages, because they only recorded their finances in the form of cash receipts and cash disbursements, and even then it was done on the notice board at the orphanage. The result of this service was that the two orphanages only recorded their finances in the form of cash inflows and cash outflows, without following the applicable standards.